"Message from a turtle": otitis with Salmonella arizonae in children. Issue 44 (November 2017) - Gavrilovici, Cristina; Pânzaru, Carmen-Valentina; Cozma, Sebastian; Mârţu, Cristian; Lupu, Vasile Valeriu; Ignat, Ancuta; Miron, Ingrith; Stârcea, Magdalena
Abstract: Rationale: Salmonella enterica subsp arizonae is a common gut inhabitant of reptiles (snakes are the most common reservoir, but it also occurs in turtles). Alhough human cases owing to this organism are exceedingly rare, it may occasionally infect young infants and immunocompromised individuals with a history of intimate associations with reptiles. Our case is the 20th one among the infections with S arizonae in children, but the 2nd one of otitis and the first of mastoiditis. The other cases had different anatomical locations, such as gastroenteritis, osteomyelitis, meningitis, ankle infection, wound infection, and sinusitis. Patient concerns and diagnosis: We report a rare case of otitis with Salmonella in a previously healthy adolescent, which was most likely acquired after bathing in a lake. The ear infection was complicated with mastoiditis. Audiometric testing showed a moderately conductive hearing loss (60 dB on pure-tone average). Intervention: Standard therapy for S arizonae was initiated. The surgery revealed a "hidden" cholesteatoma. Surgical management comprised of canal wall up mastoidectomy with attico-antrotomy and posterior tympanotomy followed by tympanoplasty. Outcomes: Daily postoperative dressing care of the incision, along with antibiotic lavage of the external auditory canal packing, ensured a favorable evolution. The functional gain was important; the 1-month postsurgical pure tone audiogram indicated nearly normal hearing (a mean of 25 dB for air conduction thresholds). Lesson: Salmonella enterica serotype arizonae is a rare cause of human infection, being a common organism in reptiles, like snakes and turtles. Young children are at a particular risk for acquiring such infections. Our study might encourage further epidemiologic investigations into these infections to generate a more effective strategy among public health agencies.